2002
DOI: 10.1046/j.1365-2168.2002.02275.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and sexual dysfunction following laparoscopically assisted and conventional open mesorectal resection for cancer

Abstract: Laparoscopically assisted rectal resection is associated with a higher rate of male sexual dysfunction, but not bladder dysfunction, compared with the open approach. This has implications, particularly for sexually active males with bulky or low rectal cancers, when deciding the best operative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
4
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(225 citation statements)
references
References 30 publications
13
192
4
16
Order By: Relevance
“…With the increasing popularity of laparoscopy, certain surgeons now perform laparoscopic assisted TME. Quah et al 74 reported that sexual dysfunction rates were higher after laparoscopic surgery than open surgery in men, but there was no difference in women. Owing to paucity of reports in the literature, it may be too early to reach any conclusion regarding the sexual function following laparoscopic TME.…”
Section: Sexual Dysfunction After Rectal Cancer Surgeriesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing popularity of laparoscopy, certain surgeons now perform laparoscopic assisted TME. Quah et al 74 reported that sexual dysfunction rates were higher after laparoscopic surgery than open surgery in men, but there was no difference in women. Owing to paucity of reports in the literature, it may be too early to reach any conclusion regarding the sexual function following laparoscopic TME.…”
Section: Sexual Dysfunction After Rectal Cancer Surgeriesmentioning
confidence: 99%
“…ED following rectal cancer surgery is further compounded by the frequent use of neoadjuvant and adjuvant radiotherapy. 74 A recent study by Mannaerts et al 66 showed that the preoperative ability to have an orgasm disappeared in 50% of males and 50% of females following multimodality rectal cancer treatment. Sexual dysfunction rates following treatment for rectal cancer are significant and should be an essential part of preoperative counseling.…”
Section: Sexual Dysfunction After Rectal Cancer Surgeriesmentioning
confidence: 99%
“…Until now, very little is known concerning sexual functioning and lower urinary tract symptoms after LTME on the long term [6,7]. A retrospective, questionnairebased study showed an ED incidence of 47% and an EJD incidence of 40% [7].…”
mentioning
confidence: 99%
“…These findings were confirmed & debated in other publications (Quah et al, 2002;Scheidbach et al, 2002;Cecil et al, 2006). It became evident that laparoscopic rectal surgery has a longer learning curve & higher conversion rate, increased circumferential margin involvement as well as poorer outcome of urinary and sexual function especially in men (Quah et al, 2002;Bretagnol et al, 2005).…”
Section: Challenges In Rectal Surgery As Identified From the Clasicc mentioning
confidence: 56%